2007
DOI: 10.1007/s00438-006-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in expression of the Escherichia coli colicin K activity gene cka is controlled by the SOS system and stochastic factors

Abstract: Phenotypic diversity provides populations of prokaryotic and eukaryotic organisms with the Xexibility required to adapt to and/or survive environmental perturbations. Consequently, there is much interest in unraveling the molecular mechanisms of heterogeneity. A classical example of heterogeneity in Escherichia coli is the subset (3%) of the population that expresses the colicin K activity gene (cka) upon nutrient starvation. Here, we report on the mechanism underlying this variable response. As colicin synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 35 publications
3
51
0
Order By: Relevance
“…Similarly, induced enteric bacteriocin promoters express low basal levels of expression and high response ratios in the current (Fig. 4) and comparable studies (Mrak et al, 2007;Norman et al, 2005;Prieto et al, 2004;Vankemmelbeke et al, 2005). Moreover, when the contributions of each of the LexA binding sites were compared, expression under a single LexA repressor resulted in higher basal levels and lower response ratios (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Similarly, induced enteric bacteriocin promoters express low basal levels of expression and high response ratios in the current (Fig. 4) and comparable studies (Mrak et al, 2007;Norman et al, 2005;Prieto et al, 2004;Vankemmelbeke et al, 2005). Moreover, when the contributions of each of the LexA binding sites were compared, expression under a single LexA repressor resulted in higher basal levels and lower response ratios (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…However, in the alternative single mutant (2/+), the A tract is not present and the TA sequence forms a rigid structure. This observation may explain the decreased levels of luminescence measured and is supported by Mrak and colleagues (Mrak et al, 2007), who showed that T substitutions in the A tract of the distal SOS box (the AAAA motif was altered to ATAT) result in a decrease in gene expression, signifying the importance of the A motif. Interestingly, the single SOS box found in the colicin Ib promoter lacks A or T tracts (Table 3), and is thus less bendable, which might explain the lower response ratio observed (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations